Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 month ago

help with this math problem?

Attachment image

1 Answer

Relevance
  • Favorite Answer

    (x^2 - x + 2) * (ax + b + (cx + d)/(x^2 - x + 2)) = 2x^3 - 3x^2 + 4x - 2

    (x^2 - x + 2) * (ax + b) + cx + d = 2x^3 - 3x^2 + 4x - 2

    ax^3 + bx^2 - ax^2 - bx + 2ax + 2b + cx + d = 2x^3 - 3x^2 + 4x - 2

    ax^3 = 2x^3

    a = 2

    bx^2 - ax^2 = -3x^2

    b - a = -3

    b - 2 = -3

    b = -1

    2a - b + c = 4

    4 - (-1) + c = 4

    4 + 1 + c = 4

    5 + c = 4

    c = -1

    d = -2

    (x^2 - x + 2) * (2x - 1 - (x + 2) / (x^2 - x + 2))

    • Login to reply the answers
Still have questions? Get your answers by asking now.